Pengembangan Media Pembelajaran Flashcard untuk Meningkatkan Motivasi Belajar Mengenal Surah Juz 29 di Taman Pendidikan Al-Qur’an - Siti Rodliyah Eka Agustina; Huda Binti Mohd Fadzil; Lina Nur Fitri Fauziyyah; Muti' Syarofani; Almi Novita (State Islamic Institute of Madura, 2024)
Recently, santri’s (students) motivation in recognizing surah, especially in Juz 29 has decreased. Therefore, as the importance of recognizing surah, teachers need to design new strategies or tools to boost santri’s motivation. This research tries to develop Astati' an A'rif Surah (ARIFAH) flashcard as an innovation to increase motivation to recognize surah in Juz 29. This research aims to describe the development process of ARIFAH flashcard which consists of five stages. Adopting the ADDIE model development theory, this research employs Research and Development (R&D) focusing on the main five stages: analysis, design, development, implementation, and evaluation. Qualitative data will be analyzed descriptively, while quantitative data will be analyzed statistically. The developed learning media has been validated by media experts and material experts. In addition, the developed learning media has also been tested on tahfiz program santri who will memorize juz 29. The results showed that the percentage of validation test results to material experts was 87.5% with an excellent category. The results of the validation test for the media experts showed an exceptional category with a percentage of 100%. The use of media on santri gets 98.6% with an excellent category. At the same time the average motivation learning of santri gets 98.1% with an exceptional category. Based on the questionnaire results, the santri experienced an increase in motivation due to interesting and fun learning media. Therefore, it can be concluded that ARIFAH flashcards are very feasible to use as a learning media.